Metformin in prevention and treatment of antipsychotic induced weight gain: a systematic review and meta-analysis - De Silva, V.A.; Suraweera, C.; Ratnatunga, S.S.; Dayabandara, M.; Wanniarachchi, N.; Hanwella, Raveen (Springer Nature, 2016)
Background: Overweight and obesity are highly prevalent in people with severe mental illness (SMI). Antipsychotic-induced weight gain (AIWG) is one of the most commonly reported and distressing side effects of treatment and people living with SMI place a high value on the avoidance of this side effect. Metformin is the most effective pharmacological intervention studied for the prevention of AIWG yet clear guidelines are lacking and evidence has not translated into practice. The aim of this research was to develop a guideline for the use of metformin for the prevention of AIWG. Study Design: The appraisal of guidelines for research and evaluation II instrument (AGREE II) was followed for guideline development. Literature was reviewed to address key health questions. The certainty of evidence was evaluated using GRADE methodology and an evidence-to-decision framework informed the strength of the recommendations. A consensus meeting was held where the algorithm and strength of recommendations were agreed. An independent external review was conducted involving experts in the field, including patient and public partners. Study Results: Metformin is the only pharmacological agent that has demonstrated efficacy for preventing AIWG. Co-commencement with antipsychotic medicines can reduce the extent of weight gain by 4.03 kg (95% CI −5.78 kg to −2.28 kg) compared to controls. A guideline for the use of metformin for the prevention of AIWG was developed with specific recommendations for co-commencement of metformin at initiation with an antipsychotic or commencement if certain criteria are present. Core recommendations were graded as strong by consensus agreement. Conclusions: This is the first published evidence-based guideline using the AGREE II framework and GRADE methods for the use of metformin to prevent AIWG incorporating recommendations for co-commencement. Implementation and evaluation of the guideline will be supported by a shared decision-making package and assessment of barriers and facilitators to implementation.
Keywords: antipsychotic; metformin; prevention; severe mental illness; weight gain